Cesarean Delivery and Early Breastfeeding Outcomes: A Cross-Sectional Study of EIBF and Early Postpartum Difficulties - Herawati, Ita; Hermanto, Budi; Andika, Agnes; Jumsinah, Jumsinah; Widiyanti, Lia; Tika, Ocha Gries; Marlita, Yanti (Chakra Brahmanda Lentera Institute, 2026)
Background: Cesarean section (CS) rates continue to increase globally, particularly in low- and middle-income countries (LMICs) such as Indonesia. While CS is often medically indicated, it may interfere with early initiation of breastfeeding (EIBF) and early postpartum lactation. However, evidence examining both EIBF and early breastfeeding difficulties within Indonesian LMIC settings remains limited. Methods: This cross-sectional study followed STROBE guidelines and was conducted among 150 postpartum mothers within the first 10 days after delivery. Participants were recruited using consecutive sampling. Eligibility criteria included mothers aged ≥18 years, live singleton birth, and clinical stability. Data were collected using a structured Breastfeeding Initiation and Early Lactation Difficulty Questionnaire adapted from validated instruments (Cronbach’s α = 0.82). Chi-square tests were used to assess associations, with assumptions verified (expected cell count ≥5). Odds ratios (ORs) with 95% confidence intervals (CIs) were calculated to estimate effect size. Results: CS was significantly associated with failure to perform EIBF (OR = 214.79; 95% CI: 27.90–1653.65; p < 0.001). Mothers undergoing CS were also more likely to experience breastfeeding difficulties during the first 10 days postpartum (OR = 17.26; 95% CI: 6.24–47.74; p < 0.001). Conclusion: CS delivery is strongly associated with delayed EIBF and increased early breastfeeding difficulties. Structured post-cesarean lactation support integrated into surgical recovery protocols is recommended, particularly in LMIC settings.